2021
DOI: 10.31234/osf.io/93pbk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two of a kind or distant relatives? A multimethod investigation of the overlap between personality traits and character strengths

Abstract: Allport’s (1927) distinction of personality devaluated (personality) and personality evaluated (character) can still be found in today’s psychological landscape. The present study compares the Five-Factor Model of personality and the VIA-classification of character strengths across two methods (self- and peer-reports) and across two levels of abstraction (domains/factors and scales/facets). A sample of 152 participants and 152 peer-raters completed the NEO-Personality Inventory Revised and the VIA Inventory of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Although the FFM provides an overall description of a person, character strengths are narrower, specific traits describing the “good person” (McGrath et al., 2020 ). Accordingly, a considerable overlap with the personality traits of the FFM is to be expected, but empirical studies have shown that character strengths and FFM personality traits are not redundant (McGrath et al., 2020 ; Noftle et al., 2011 ; Ruch et al., 2021 ). Furthermore, character strengths incrementally explain variance in various work, educational, and behavioral outcomes beyond FFM personality traits (e.g., Harzer et al., 2021 ; Ruch et al., 2017 ; Wagner & Ruch, 2021 ).…”
Section: Character Strengths and Intelligencementioning
confidence: 99%
“…Although the FFM provides an overall description of a person, character strengths are narrower, specific traits describing the “good person” (McGrath et al., 2020 ). Accordingly, a considerable overlap with the personality traits of the FFM is to be expected, but empirical studies have shown that character strengths and FFM personality traits are not redundant (McGrath et al., 2020 ; Noftle et al., 2011 ; Ruch et al., 2021 ). Furthermore, character strengths incrementally explain variance in various work, educational, and behavioral outcomes beyond FFM personality traits (e.g., Harzer et al., 2021 ; Ruch et al., 2017 ; Wagner & Ruch, 2021 ).…”
Section: Character Strengths and Intelligencementioning
confidence: 99%
“…This list of 24 character strengths has been used in numerous studies. It has been shown that character strengths are valued across cultures (e.g., Pievsky & McGrath, 2022), robustly related to well-being (e.g., Park et al, 2004;Wagner et al, 2020), and overlapping but not redundant with Big Five and HEXACO personality domains and facets Ruch et al, 2022). In addition, Peterson and Seligman (2004) describe character strengths as trait-like yet malleable.…”
Section: Which Positive Personality Traits Do People Want To Change?mentioning
confidence: 99%
“…Peterson and Seligman (2004) understand character as a multidimensional, relatively stable, but malleable, construct and suggest a classification of six universal core virtues and 24 related character strengths (VIA classification). Character strengths are distinguishable from broader personality traits, such as the Big Five personality traits (McGrath et al, 2020;Ruch et al, 2023). A great number of studies support the important role of character strengths possession and application in the work context (e.g., Heintz & Ruch, 2020;Lavy et al, 2017).…”
Section: Study 1: Flexibility and Well-being Initial Examinationmentioning
confidence: 99%